A evasão nos cursos superiores de tecnologia em uma Faculdade do Interior Paulista - SUFI, Rosângela de Carvalho (2018)
The present study presents a study carried out at a public technology college in the interior of the state of São Paulo, offering courses at a higher level. The research is linked to the Research Line "Public Policies in Education, Formative Processes and Diversity" and has the general objective of investigating the causes of evasion in the Higher Education of Technology through the perception of the evaded students. As specific objectives, it was tried to present the historical process of expansion of technological education of higher level, relating it to the phenomenon of evasion; to analyze the phenomenon of evasion from research on this topic and from current data, taken from documentary sources; identify, from the perspective of the evaded students, the reasons that led them to evade. It is chosen as a problem of this research the understanding of the causes that led students to evade in a public institution, located in the interior of São Paulo. In the research, we adopted a qualitative approach, of the case study type, and used, as instruments of data collection, the bibliographic survey, the documentary analysis and the semistructured interviews. For the analysis of the data, we base ourselves on some of the assumptions of the content analysis of Bardin (2011), especially with regard to the process of categorization of abstracted contents from the instruments. The collected data made it possible to conclude that there are several factors that contribute to the student left the college, and were categorized into three: individual factors, institutional factors and social factors. The relevance of this work is justified by its contribution in the presentation of results that may guide the development of strategies by the teaching institution, in order to reduce the dropout rates, thus contributing to the student's stay in college.